EclipseNB: A Network of Low‐Cost GNSS Receivers to Study the Ionosphere - A. Kashcheyev; B. Nava; C. Watson; P. T. Jayachandran; R. B. Langley (Space Weather)
Abstract This work aims to demonstrate that dense networks of low‐cost dual‐frequency global navigation satellite systems (GNSS) receivers can be used to retrieve ionospheric electron content with almost the same level of accuracy as scientific‐grade GNSS receivers. A network of 15 GNSS receivers called EclipseNB was designed and installed in New Brunswick, Canada to study ionospheric structure and dynamic behavior, including the response of the ionosphere to the total solar eclipse in April 2024. EclipseNB observations during the solar eclipse and the extreme geomagnetic storm in May 2024 are presented. The status and the future of the network are discussed.